2017
DOI: 10.1108/qrj-12-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

The role of triangulation in sensitive art-based research with children

Abstract: Purpose The purpose of this paper is to highlight the critical role of triangulation to create authentic analytical frameworks amidst contradictory participant narratives in sensitive art-based research (ABR) with children. Design/methodology/approach Multiple qualitative case study research included three months of participant observation, individual semi-structured teacher interviews and open-ended art-based interviews using the Draw-Write-Narrate method (Ogina and Nieuwenhuis, 2010) with upper primary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Drawing on the use of triangulation in arts-based research (c.f. Vanner & Kimani, 2017), these different forms of data will be reviewed and coded for the presence of multiple, emergent worldviews. In order to provide corroborating evidence triangulating the data and creating opportunities to validate study findings, the qualitative data will be brought in conversation with the quantitative data from surveys and evaluation data.…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
“…Drawing on the use of triangulation in arts-based research (c.f. Vanner & Kimani, 2017), these different forms of data will be reviewed and coded for the presence of multiple, emergent worldviews. In order to provide corroborating evidence triangulating the data and creating opportunities to validate study findings, the qualitative data will be brought in conversation with the quantitative data from surveys and evaluation data.…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
“…In this case, Ishiguro et al (2016) stated that learners change their viewing strategies in art appreciation after a course of education in which the mean duration of addiction decreases when one is viewing photographs with recognizable subjects. The critical role of triangulation to create authentic analytical frameworks amidst contradictory participant narratives in sensitive art-based research (ABR) with children make them appreciate or not appreciate what art is (Vanner & Kimani, 2017). If one truly understands one-piece or form of art, it can be assumed that they are also be able to appreciate it.…”
Section: Art Appreciationmentioning
confidence: 99%
“…The emphasis on the meaning that can be elicited through the arts and the relational value of artistic productions are converging, along with a posture of sensitive listening (see Bagnoli, 2009;Boydell et al, 2012;C. Mitchell et al, 2011;Vanner & Kimani, 2017). Arts-based methods have been used to give a voice to the experience of children, even very young ones, in relation to sensitive issues like inclusion, fear, life after trauma, and even on the very issue of having a voice or not, in healthcare settings and in education (see for example Akesson et al, 2014;Blaisdell et al, 2019;Clark, 2005;Coad, 2007;Driessnack, 2006).…”
Section: Toward a Clinical And Arts-based Approach To Research With Childrenmentioning
confidence: 99%
“…We know, from Spratling et al (2012), for example, that it is possible for children to talk about their experiences in interviews but little is known about how to foster this. Researchers have also highlighted the challenges encountered in working with children on sensitive issues (Akesson et al, 2014;Vanner & Kimani, 2017). Research has shown that children will mask or withhold negative or emotionally disturbing information and focus on the present in verbal interviews as Docherty and Sandelowski (1999) have pointed out.…”
Section: Introductionmentioning
confidence: 99%